2017
DOI: 10.1186/s12881-017-0395-6
|View full text |Cite
|
Sign up to set email alerts
|

NT5C2 novel splicing variant expands the phenotypic spectrum of Spastic Paraplegia (SPG45): case report of a new member of thin corpus callosum SPG-Subgroup

Abstract: BackgroundHereditary Spastic Paraplegia (HSP) is a genetically heterogeneous group of neurodegenerative diseases. Thin Corpus Callosum (TCC) associated HSP is a distinguished subgroup of complex forms. Purines and pyrimidine, the basic DNA and RNA components, are regulating the cell metabolism, having roles in signal transduction, energy preservation and cellular repair. Genetic defects in nucleotide metabolism related genes have been only recently implicated in brain and neurodegenerative diseases’ pathogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 16 publications
(22 reference statements)
2
21
0
Order By: Relevance
“…NT5C2 has also been implicated in schizophrenia, leukemia, and hypertension (Aberg et al, ; Kelly et al, ; Meyer et al, ), but the loss‐of‐function (frameshift, nonsense, splice site) mutations identified by Novarino et al () establish this as the causative gene in SPG45. Underscoring this association, a further autosomal recessive splice site mutation in NT5C2 has also been reported in two more siblings with SPG45 (Elsaid et al, ).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…NT5C2 has also been implicated in schizophrenia, leukemia, and hypertension (Aberg et al, ; Kelly et al, ; Meyer et al, ), but the loss‐of‐function (frameshift, nonsense, splice site) mutations identified by Novarino et al () establish this as the causative gene in SPG45. Underscoring this association, a further autosomal recessive splice site mutation in NT5C2 has also been reported in two more siblings with SPG45 (Elsaid et al, ).…”
Section: Introductionmentioning
confidence: 85%
“…Novarino et al () studied the family reported by Dursun et al () and eight individuals from four additional families with SPG45. Recently, Elsaid et al () reported two additional brothers of a consanguineous Qatari family harboring a novel homozygous NT5C2 splice site mutation. They were unique to all other patients reported so far with SPG45 in that they displayed persistent early truncal hypotonia, dysarthria, and variable‐sized patches of skin brownish discoloration that appeared at 6 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Among all other patients reported so far with CP, they were unique in that they displayed persistent early in 2017, truncal hypotonia, dysarthria, and variable-sized patches of brownish skin staining at early stage of life (Elsaid et al, 2017). Straussberg describes the clinical, radiologic, and genetic findings in three affected members of the consanguineous family from Arab region CP belonging to that harbors a novel mutation in NT5C2 (c.1379T > C; p.Leu460Pro) (Elsaid et al, 2017). Moreover, recently exon rearrangement c.771 + 573_814-298del reported in the in NT5C2 loci in a family with a complex genetic hereditary spastic paraplegias (Darvish et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…Recently Elsaid et al reported a consanguineous Qatari family having a novel homozygous c.1159 +1G > T in NT5C2 splice site mutation (NM_012229.4/ NM_001134373.2). Among all other patients reported so far with CP, they were unique in that they displayed persistent early in 2017, truncal hypotonia, dysarthria, and variable-sized patches of brownish skin staining at early stage of life (Elsaid et al, 2017). Straussberg describes the clinical, radiologic, and genetic findings in three affected members of the consanguineous family from Arab region CP belonging to that harbors a novel mutation in NT5C2 (c.1379T > C; p.Leu460Pro) (Elsaid et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation